2010
DOI: 10.1007/s10640-010-9365-6
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with Ignored Attributes in Choice Experiments on Valuation of Sweden’s Environmental Quality Objectives

Abstract: Using a choice experiment, this paper investigates how Swedish citizens value three environmental quality objectives. In addition, a follow-up question is used to investigate whether respondents ignored any attributes when responding. The resulting information is used in the model estimation by restricting the individual parameters for the ignored attributes to zero. When taking the shares of respondents who considered both the environmental and the cost attributes (52-69 percent of the respondents) into accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
3
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 25 publications
8
108
3
11
Order By: Relevance
“…Building on encouraging results from past research on ANA in environmental economics [21,45,46] and health [47][14], our study confirms that ANA is a valuable tool for analyzing clinical decision making. To the authors' knowledge, this study is the first to suggest that less experienced psychiatrists may be inappropriately influenced by a patient's genetic information in their clinical decision making.…”
Section: Discussionsupporting
confidence: 74%
“…Building on encouraging results from past research on ANA in environmental economics [21,45,46] and health [47][14], our study confirms that ANA is a valuable tool for analyzing clinical decision making. To the authors' knowledge, this study is the first to suggest that less experienced psychiatrists may be inappropriately influenced by a patient's genetic information in their clinical decision making.…”
Section: Discussionsupporting
confidence: 74%
“…However, as opposed to our hypothesis 6 stated above, it has been argued in the literature, that when merely asked to state non-attendance there is no incentive to provide a truthful answer, regardless of the setting being hypothetical or real (e.g. Hess and Hensher, 2010;Alemu et al, 2013;Carlsson et al, 2010). Instead it is suggested to rely on non-attendance being inferred from the model.…”
Section: Hypotheses On Attribute Processing and Self-imagecontrasting
confidence: 60%
“…Or perhaps even more interesting; do the estimates represent preferences? Hess et al (2012), Alemu et al (2013) and Carlsson et al (2010) suggest that rather than ignoring attributes completely, respondents might simply put less weight on attributes they claim to have ignored. They base this on the fact that the most often ignored non-monetary attribute also receives the lowest preference ranking in their estimated utility model.…”
Section: Parametric Resultsmentioning
confidence: 99%
“…Most of the previous studies showed that the CE results will be biased if the analyst did not deal with the attribute non-attendance problem, however, not all studies hold the same view [40,41]. A stated non-attendance(SNA) method (Hensher et al [42], Carlsson et al [43] and Chalak et al [44]) or an inferred non-attendance (INA) method (Hess et al [45] and Hensher et al [46]) can be used to identify attribute non-attendance.…”
Section: Discussionmentioning
confidence: 99%